Developing Coalitions in a Tourism-Based Economy: The New Orleans Joint Center for Tourism - Brooks, Jane; Lacho, Kenneth (Téoros)

(untitled) (Université du Québec à Montréal, 1991)
The New Orleans Vieux Carre is an attraction to tourists, yet the growth of tourism may well be a threat to its very survival. The formation of the JCT and Cultural Treasures Group reflects the efforts of people who are concerned about the preservation of the Vieux Carre as an intact historic neighborhood. The reaching out to tourism-related organizations reflects an attempt to work with these groups in developing a mechanism for controlling growth of the tourism industry, yet at the same time preserving an historic neighborhood. The problems of the JCT in achieving its goals are simply due to the lack of resources, central control, and perceived inattention by city government.The difficulty of the JCT to progress towards its objectives has resulted in a spinoff subgroup. This group is smaller, more compact members have similar values, and belong to organizations directly related to the Vieux Carre. Its prognosis is uncertain at this time.